Clinical and ultrasonic estimation of fetal weight - Brink, Derek Montagu (Department of Obstetrics and Gynaecology, 2017)
Several clinical situations occur in obstetrics where it is useful to make an accurate assessment of fetal weight prior to delivery. A foreknowledge of the mass of the fetus can influence management in circumstances complicated by, for example, a previous caesarean section, a breech presentation, a compromised fetus of borderline viability and a diabetic pregnancy at term. Researchers have attempted to estimate fetal weight by assaying oestriol, human placental lactogen, and pregnanediol. These parameters have been found to be of limited value because of the indirect measurement of fetal mass. Since the introduction of ultrasound scanning techniques to obstetrics in the mid- 1960's, it has become possible to visualise the fetus and to make direct measurements of fetal anatomy. By using ultrasound, workers have tried to predict fetal weight by measuring fetal heart volume, hourly urine production, trunk diameter, circumference and placental volume. At present various combinations of head circumference (HC), biparietal diameter (BPD), femur length (FL), and abdominal circumference (AC) are the most commonly used measurements which, when used in different formulas and read off tables estimate fetal weight. Recently the gestational age (GA) has been incorporated into formulas specifically applied to small for gestational age (SGA), appropriate for gestational age (AGA), and large for gestational age (LGA) fetuses. A sonographic estimation of fetal weight based on a model of fetal volume has also been developed. It was generally believed that with the refining of ultrasonic estimation of fetal weight an accurate assessment of fetal mass could, at last, be made. Some investigators believe that the ultrasound estimation of fetal mass is more accurate than clinical assessment. In contrast other workers have shown that the accuracy of clinical examination is comparable to ultrasound determination in estimating fetal weight.